2019
DOI: 10.1097/meg.0000000000001590
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the distribution of etiologies of cirrhosis among patients referred for liver transplantation over 11 years in Iran

Abstract: Background and aim: Cirrhosis is a major public health problem worldwide. The prevalence of cirrhosis is various in different geographical regions. The aim of the present study was to determine the distribution of the etiologies of cirrhosis and their proportional changes through recent 11 years in Iran. Methods: In this retrospective, observational study, the data of cirrhotic patients who have been listed for liver transplantation in the Namazi Transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In addition, the proportion of some cirrhosis etiologies, such as non-alcoholic steatohepatitis (NASH) cirrhosis, has increased over time in the waitlist for LT, while the proportion of some cirrhosis etiologies, such as HBV cirrhosis, has decreased worldwide. 8 - 10 Similar to the frequency of patients with ESLD, the trend in the proportion of different etiologies on the waitlist for LT is not necessarily in accordance with the trend in the proportion of different etiologies in liver‐transplanted patients. The other important issue is the survival rate of LT patients.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the proportion of some cirrhosis etiologies, such as non-alcoholic steatohepatitis (NASH) cirrhosis, has increased over time in the waitlist for LT, while the proportion of some cirrhosis etiologies, such as HBV cirrhosis, has decreased worldwide. 8 - 10 Similar to the frequency of patients with ESLD, the trend in the proportion of different etiologies on the waitlist for LT is not necessarily in accordance with the trend in the proportion of different etiologies in liver‐transplanted patients. The other important issue is the survival rate of LT patients.…”
Section: Introductionmentioning
confidence: 99%
“…The main causes of cirrhosis include viral infections such as hepatitis B virus (HBV) and hepatitis C virus (HCV), alcohol-induced fatty liver disease (AFLD), cholestasis-related conditions like primary sclerosing cholangitis (PSC), autoimmune hepatitis (AIH), and metabolic disorders like non-alcoholic fatty liver disease (NAFLD). While viral infections were previously known to be the most common causes of liver cirrhosis, their prevalence has decreased due to HBV vaccination (2). On the other hand, the prevalence of cirrhosis due to cholestasis, AIH, and, specifically, non-alcoholic steatohepatitis (NASH) has been increasing in recent years (2).…”
Section: Introductionmentioning
confidence: 99%
“…While viral infections were previously known to be the most common causes of liver cirrhosis, their prevalence has decreased due to HBV vaccination (2). On the other hand, the prevalence of cirrhosis due to cholestasis, AIH, and, specifically, non-alcoholic steatohepatitis (NASH) has been increasing in recent years (2). It has been suggested that immune-mediated mechanisms play a crucial role in the development of these types of cirrhosis, with autoantibodies being prominent in AIH, PSC, and NASH cirrhosis (3).…”
Section: Introductionmentioning
confidence: 99%
“…Liver cirrhosis is recognized as the 11th leading cause of mortality in the world [1]. Cirrhosis is the last pathological outcome of different chronic liver disorders, and newer research has established that fibrosis is the starter of cirrhosis [2][3][4]. Many types of factors are involved in the beginning and development of liver fibrosis and cirrhosis [3].…”
mentioning
confidence: 99%